Remarks on Parametric Surface Waves in a Nonlinear and Non-Ideally Excited Tank - Navarro, Helio A.; Balthazar, José Manoel [UNESP]; Krasnopolskaya, Tatyana S.; Shvets, Aleksandr Yu.; Chavarette, Fábio Roberto (Asme-amer Soc Mechanical Eng, 2012)
We studied free surface oscillations of a fluid in a cylinder tank excited by an electric motor with limited power supply. We investigated the possibility of parametric resonance in this system, showing that the excitation mechanism can generate chaotic response. Numerical experiments are carried out to present the existence of several types of regular and chaotic attractors. For the first time powers (power of the motor, power consumed by the damping force under fluid free surface oscillations, and a total power) are calculated, investigated, and shown for different regimes, regular and chaotic ones for parametric resonance interactions. [DOI: 10.1115/1.4005844]
Keywords: non-ideal power sources; parametric resonance; chaos